2018
DOI: 10.1016/j.dib.2018.08.064
|View full text |Cite
|
Sign up to set email alerts
|

Data on optimization of production parameters on Persea Americana (Avocado) plant oil biodiesel yield and quality

Abstract: Biodiesel has continued to receive enormous patronage from world energy demand as a result of its renewable nature, low toxicity, rapid degradation, robust fuel performance and low emission characteristics and its overall environmental friendliness.Hence, these data showed the optimization of temperature, catalyst concentration and type of catalyst, alcohol type and alcohol to oil molar ratio and reaction time on Avocado plant oil biodiesel yield and quality produced via alkali-catalyzed transesterification re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Our results are in line with those demonstrated for avocado biodiesel where higher heat of combustion was detected in biodiesel than in oil (40.106 and 39.485 kJ•kg −1 , respectively) [36]. Similar heating value was also demonstrated for avocado biodiesel (40.365 kJ•kg −1 ) [38].…”
Section: Biodiesel Physical Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with those demonstrated for avocado biodiesel where higher heat of combustion was detected in biodiesel than in oil (40.106 and 39.485 kJ•kg −1 , respectively) [36]. Similar heating value was also demonstrated for avocado biodiesel (40.365 kJ•kg −1 ) [38].…”
Section: Biodiesel Physical Characterizationsupporting
confidence: 92%
“…In addition, the biodiesel complies with the specification allowed by International Standard (EN 14214 2003, method IS0 3104) of 3.5-5.0 mm 2 •s −1 at 40 • C [35]. Lower viscosity values have been demonstrated for avocado biodiesel (4.42 mm 2 •s −1 and 3.75 mm 2 •s −1 ) [27,38] and avocado seed biodiesel and 3.94 and 4.42 mm 2 •s −1 [19]. On the other hand, another study demonstrated a higher value of viscosity for avocado seed biodiesel (5.02 mm 2 •s −1 ) [18].…”
Section: Biodiesel Physical Characterizationmentioning
confidence: 99%
“…Ethanol was used as the extracting solvent. The solvent choice was based on a study by (Anawe and Folayan, 2018), which reported a higher yield for avocado pulp extraction with ethanol when compared with other solvents. The extracted oil was degummed using phosphoric acid, and this was carried out by adding 20 ml of phosphoric acid to 300 g of the extracted oil and the mixture heated and continuously stirred for 30 min and allowed to settle for 1 h after which the phospholipids was separated from the degummed oil.…”
Section: Oil Extraction and Pre-treatmentmentioning
confidence: 99%
“…As a consequence, it is necessary to investigate inedible options for the production of second-generation biofuels, so as not to compete with food uses [59]. In this context, several documents highlight the potential of different type of avocado oils for biodiesel production through, mainly, catalyst-assisted alcoholysis of its oil fraction [60][61][62][63][64]. It is also known as the transesterification reaction of triglycerides and the esterification of free fatty acid [65].…”
Section: Biodieselmentioning
confidence: 99%